Are cities good for health? A study of the impacts of planned urbanization in China. (18th March 2019) - Hou, Bo; Nazroo, James; Banks, James; Marshall, Alan
Abstract: Background: Urbanization in developing countries is usually accompanied by migration to cities, making it a challenge to unpack the independent relationships between migration, urbanization and health, particularly in the presence of health-selective migration. Since 1978, unprecedented planned urbanization has taken place in China and further increases to the urban population are expected. This paper explored the impacts of urbanization in China through a comparative study of in situ urbanized population. Methods: Using the China Health and Retirement Longitudinal Study (CHARLS), a nationally representative dataset for people aged 45 years or older, we compared self-assessed general health, depressive symptoms and waist circumference among three groups: (i) in situ urbanized-rural residents; (ii) rural residents; and (iii) urban residents. Using a model informed by the literature on the social determinants of health in later life, we investigated the patterning and drivers of differences in health outcomes between these three groups, in order to explore the impact of urbanization independent of the impact of migration. Results: There are consistent advantages in health and less depression among urbanized-rural residents compared with the rural group; and this group has even better health outcomes than the urban group after adjusting for early life differences. However, this relationship is reversed for waist circumference. Socioeconomic circumstances and factors related to a planned urbanization partly explain these effects. Conclusions: Urbanization in China has, on average, had an independent and positive effect on health and well-being. Planned urbanization could benefit people's health in developing countries. It is likely that improved infrastructure is a key driver.